Peran Asosiasi Merek Berdasarkan Fungsi Merek dalam Upaya Meningkatkan Kesediaan Pembelian Perluasan Merek Betadine pada Kategori Produk Lainnya - Nindria Untarini (BISMA (Bisnis dan Manajemen), 2018)
This paper studies the deminsions of equity brand. Focusing on the functions or value of the brand as perceived consumers. In this way, four categories of functions are indentified: guarantee, personal identification, social identification and status. It has objective, to know the influence of brand associations based on function toward consumers willingness to buy brand extensions. By way hypotheses, it has been proposed that these functions have positive influence on the consumers willingness to buy brand extensions. The hypotheses have been tested in the Surabaya antiseptic drug market and were partially supported and simultaneously supported. The result obtained confirm the convenience of analyzing brand associations separately and simultaneously enable the ascertaining of brand associations that are most relevant in order to attain certain the consumers willingness to buy  brand extensions. Future research would also be interesting to conduct a comprehensive multicategory analysis in order to indetify the relative importance of various brand fuctions in different product categories, the more various sampling techniques and more samples, and selection of other brands so that to represent all users antiseptic drug in Surabaya